Efektivitas Penegakan Hukum Terhadap Pelaku Penambangan Pasir Tanpa Izin (Studi Pada Kepolisian Resor Pangkep) - Badaru, Baharuddin; Razak, Askari; Umam, Wildan Syauqil; TL, A. Darmawansya (Fakultas Syariah INSURI Ponorogo, 2023)
This study aims to identify and analyze the effectiveness of law enforcement against unlicensed sand miners by the Pangkep Resort Police, and to identify and analyze the factors that impede the effectiveness of law enforcement against illegal sand miners by the Pangkep Resort Police. This type of research is empirical juridical. The research results show that the effectiveness of law enforcement against the perpetrators of sand mining without a permit by the Pangkep Resort Police is not running effectively. This is due to the understanding of the Satreskrim investigators of the Pangkep Resort Police in determining and finding the elements of crime from the perpetrator's actions, so that the investigation requires and/or presents expert witnesses to clarify the actions of the perpetrators. Factors hindering the effectiveness of law enforcement against illegal sand mining by the Pangkep Resort Police, namely; substance, structure, and legal culture. The three factors that most influence the criminal act of sand mining without a permit is the legal substance.